An Ayurvedic Approach to Manage PCOD - A Case Study - Anjali Jain,; Diksha Khathuria,; Khushwant Joshi,; Mahesh Dixit, (International Journal of Ayurveda and Pharma Research, 2022)
Polycystic Ovarian Disease (PCOD) is an endocrine disorder that causes metabolic changes in women of reproductive age. PCOD has evolved into a lifestyle disorder as a result of sedentary habits, fast food consumption, and a poor lifestyle. The precise cause of PCOD is mysterious, but high levels of insulin, hyper androgen, and LH are the main causes. PCOD symptoms include irregular menstruation, oligomenorrhea, acne, hirsutism, hair loss, obesity, and constipation. PCOD is not directly stated in the Samhita, but clinically it is similar to Aartavavaha strotas dushti, Nastaartava, Granthi, Santarponnth vyadhi, and Yonivyapad. In this present case study, a 22 year old female patient came with symptoms of irregular, delayed menstruation, scanty menses, acne on the face and hair fall. The USG report reveals polycystic patterns of both ovaries with Right ovary volume 11.6cc and Left ovary volume 11cc, both ovaries are bulky in size with increased stromal echogenicity and multiple (10-12) small follicles (2-5mm) arranged in peripheral distribution. She had taken the medication so many times but she had not been completely cured. As a result she came to our hospital for Ayurvedic treatment. Result was made on the basis of Clinical symptoms relief and USG report. So in this case study, we will look at an Ayurvedic approach in the management of Polycystic Ovarian Disease.